Dualism of Land Rights Recognition in National and Customary Legal Systems in the Perspective of Dignified Justice: Dualisme Pengakuan Hak Atas Tanah dalam Sistem Hukum Nasional dan Adat dalam Perspektif Keadilan Bermartabat - Pandapotan Damanik (Academia Open, 2025)
General Background: The recognition of land rights in Indonesia reflects a complex legal landscape marked by the coexistence of national land law and indigenous customary (ulayat) rights. Specific Background: This dualism often leads to legal uncertainty and conflicts, particularly in areas where indigenous land tenure systems remain active. Knowledge Gap: While existing studies acknowledge the presence of legal dualism, few explore it through the lens of dignified justice rooted in Pancasila values. Aims: This research aims to analyze the dualism of land rights recognition in Indonesia through the perspective of dignified justice, which upholds human dignity, balanced rights and obligations, and non-discriminatory legal treatment. Results: The findings reveal that dignified justice requires national land law to not merely coexist with, but harmonize and complement, ulayat rights to protect indigenous socio-cultural values while ensuring legal certainty. Novelty: The study introduces a framework wherein the UUPA (Basic Agrarian Law) serves as a foundational bridge to align state sovereignty over land with the recognition of living customary laws. Implications: Future regulatory frameworks must promote structural and administrative harmony, ensuring equitable land governance that respects cultural identity without compromising national legal unity. Highlights: Balances national legal certainty with indigenous land rights. Promotes harmony between customary and state law. Emphasizes justice based on Pancasila values. Keywords: Legal Dualism, Land Rights, Dignified Justice